Advances in Oxygen Evolution Electrocatalysts for Proton Exchange Membrane Water Electrolyzers. Issue 14 (17th February 2022) - Chen, Zhichao; Guo, Lei; Pan, Lun; Yan, Tianqing; He, Zexing; Li, Yue; Shi, Chengxiang; Huang, Zhen‐Feng; Zhang, Xiangwen; Zou, Ji‐Jun
Abstract: Proton exchange membrane water electrolyzer (PEMWE) technology is of interest in the context of electrocatalytic hydrogen generation from renewable energies. It has the benefits of immediate response, higher proton conductivity, lower ohmic losses, and gas crossover rate. One key step toward to large‐scale application, is the development of highly efficient, durable, and compatible anodic oxygen evolution electrocatalysts in acidic media to decrease the usage of expensive and scarce precious metals. Within this scenario, an in‐depth understanding of oxygen evolution reaction mechanisms including the adsorption evolution mechanism and lattice oxygen evolution mechanism is first provided to aid development of innovative materials and elucidate the origin of catalyst degradation. Second, recent progress in the development of oxygen evolution electrocatalysts in acid media is reviewed with an emphasis on the underlying structure–performance relationships. Third, the current application status and research progress in PEMWEs along with representative examples are discussed. Last, the remaining challenges and promising insights are proposed to inspire future studies on the development of hydrogen production technology from renewable energy. Abstract : This timeline demonstrates major developments in the application and theory for water electrolysis since its discovery. Vigorous development implies that water electrolysis promises to be a major force to promote the realization of clean energy production in human society. The accelerating pace of technological theory updates calls for timely and comprehensive reviews for both fundamental scientific research and practical applications.